P120 International similarities and differences in hereditary haemorrhagic telangiectasia (HHT) pathways reported by patients and clinicians. (12th November 2019) - Boother, EJ; von Widekind, SJ; Post, M; Kjeldsen, AD; Mager, HJ; Pagella, F; Sabba, C; Sure, U; Buscarini, E; Dupuis-Girod, S; Shovlin, CL
Abstract : Introduction and objectives: Hereditary haemorrhagic telangiectasia (HHT) results in two separate pulmonary vascular pathologies- pulmonary arteriovenous malformations (PAVMs) and pulmonary arterial hypertension (PAH). The goal of this study was to capture current practice differences in global management of HHT. Methods: Questions regarding PAVMs and pulmonary hypertension were posed to the eight centres within the European Reference Network for HHT (VASCERN) at monthly telecons and supplementary meetings. With ethical approval (16/LO/1909), an online patient questionnaire was developed using Survey Monkey, with 139 non-biased questions to capture data from HHT patients. Participants were recruited following advertisement through global HHT patient support networks. Analyses were performed in R. Results: The eight VASCERN HHT centres in France, Italy, Denmark, Germany, the Netherlands and the UK agreed that genetic testing can be used to screen for HHT, to confirm a diagnosis, or to rule out the diagnosis of HHT if the pathogenic variant is known in the family. 1 All emphasised the importance of screening all patients for pulmonary AVMs. 1 2 None of the eight screened asymptomatic patients for pulmonary hypertension based on French/Dutch series of 3, 176 HHT patients, where PAH prevalence was <2%, and pulmonary hypertension when present, was usually part of a broader picture of hepatic AVMs, anaemia, atrial fibrillation and symptoms. 465 patients with self-reported HHT completed the questionnaire and passed preset study filters. The majority were North Americans, with Europeans constituting the second largest group. 320/465 (68.8%) were female. Pulmonary AVMs were reported by 231/465 (49.7%) and hepatic AVMs by 90/465 (19.4%). Twenty-seven individuals (5.7%) reported they had pulmonary hypertension, and 15 of these (55%) reported they had hepatic AVMs. Age at self diagnosis of HHT, medical diagnosis of HHT, medical diagnosis of PAVMs, and happiness with overall management, were similar between North Americans and Europeans. The greatest disparities related to genetic testing: 33/89 (37%) UK families had been gene tested compared to 131/243 (54%) of families in other countries (Fisher exact test p=0.009). Conclusions: International consensus appears to be delivering broadly comparable clinical, but not genetic diagnostics in HHT. References: www.orpha.net/consor/www/cgi-bin/OC_Exp.php?lng=EN&Expert=774. Orphanet J Rare Dis 2018:13(1);136.